KARAKTERISTIK KEPEMIMPINAN PT ENERGI SEJAHTERA MAS DUMAI - Vadhillah, Syukra; Tobari, Tobari (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2016)
This qualitative research was done to describe the leadership characteristic of PT Energi Sejahtera Mas Dumai. We used interview and documentation to collect the data. The interview was done with the two ESM officers. The documentation was done to record the interview. The results obtained indicate that the leader of ESM had the following characters: charismatics, respect to people, discipline, wisdom, sincere, empowering unity, developing officersâ€™ responsibility, encouragingi, and emphaty. Â Keyword: Leadership Characteristic, PT Energi Sejahtera Mas, Dumai